Sound technology and the American cinema : perception, representation, modernity - Lastra, James (New York : Columbia University Press, 2000)
- Introduction##- Discourse/Device/Practice/Institution: Representational Technologies and American Culture ##- Inscriptions and Simulations: The Imagination of Technology ##- Performance, Inscription, Diegesis: The Technological Transformation of Representational Causality ##- Everything But the Kitchen Sync: Sound and Image Before the Talkies ##- Sound Theory ##- Standards and Practices: Aesthetic Norm and Technological Innovation in the American Cinema ##- Sound Space and Classical Narrative.
Includes bibliographical references (p. [223]-263) and index.
boek